학습자용 영어 연어사전 비교 분석 - 정영국(Jeong, Young-kuk) (한국사전학, 2015)
Recently the study on collocations is getting a high value in foreign language education fields with the sparkling interest in communicative use of foreign languages. In time for the needs of dictionary users, three world-wide prestigious publishers, Oxford University Press, Macmillan, and Longman, have published English collocations dictionaries based on copora analysis since 2002. These dictionaries are Oxford Collocations Dictionary for Students of English (OCD, 2002, 2009), Macmillan Collocations Dictionary for Learners of English (MCD, 2010), and Longman Collocations Dictionary and Thesaurus (LCD, 2013). This paper compares these three dictionaries focusing on the number of headwords, sense division of the headwords, arrangement of collocates, and presentation of the meaning of collocations. It is found out that OCD carries around 9,000 headwords, which are about two times of the headwords of MCD or LCD. While OCD and MCD arrange collocates alphabetically, LCD presents collocates according to frequency of collocations. KCI Citation Count: 0